CSF-1-induced DC-SIGN+ macrophages are present in the ovarian endometriosis - Li Xiaocui; Hong Wei; Cai Yunlang; Zheng Zhenzhen; An Min (BMC, 2022)
Abstract Background Researchers have found that macrophages are the predominant cells in the peritoneal fluid (PF) of endometriosis patients. CSF-1 has been found to accumulate in the lesions and PF of endometriosis patients, and CSF-1 induces THP-1-derived macrophages to polarize toward a CD169+ DC-SIGN+ phenotype. Does the cytokine CSF-1 induce monocytes to differentiate into macrophages with a DC-SIGN+ phenotype in endometriosis? Methods The level of CSF-1 in the endometrium of control subjects, and the eutopic, and ectopic endometrium of endometriosis patients was evaluated by real-time polymerase chain reaction (qRT-PCR) and was determined by enzyme-linked immunosorbent assay (ELISA) in the PF of control and endometriosis patients. CSF-1 expression was examined with a MILLIPLEX MAP Mouse Cytokine/Chemokine Magnetic Bead Panel. DC-SIGN+ macrophages were detected by immunohistochemical staining of tissues and flow cytometric analysis of the PF of control subjects (N = 25) and endometriosis (N = 35) patients. The phenotypes and biological activities of CSF-1 -induced macrophages were compared in an in vitro coculture system with peripheral blood lymphocytes from control subjects. Results In this study, we found that the proportion of DC-SIGN+ CD169+ macrophages was higher in the abdominal immune microenvironment of endometriosis patients. CSF-1 was primarily secreted from ectopic lesions and peritoneum in mice with endometriosis. In addition, CSF-1 induced the polarization of macrophages toward a DC-SIGN+ CD169+ phenotype; this effect was abolished by the addition of an anti-CSF-1R antibody. CSF-1 induced the generation of DC-SIGN+ macrophages, leading to a depressed status of peripheral blood lymphocytes, including a high percentage of Treg cells and a low percentage of CD8+ T cells. Similarly, blockade with the anti-CSF-1R antibody abrogated this biological effect. Conclusions This is the first study on the role of DC-SIGN+ macrophages in the immune microenvironment of endometriosis. Further study of the mechanism and biological activities of CSF-1-induced DC-SIGN+ macrophages will enhance our understanding of the physiology of endometriosis. Graphical Abstract